Dietary Protein and Muscle in Aging People - Matteo Cesari (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This Special Issue of Nutrients, entitled "Dietary Proteins and Muscle in Aging People", welcomes the submission of manuscripts either reporting original research or reviewing the scientific literature. Manuscripts should focus on the mechanisms linking dietary protein with muscle quality and quantity. Articles presenting results from clinical trials testing protein interventions on muscle mass and function are welcome. The Special Issue aims at including articles spanning different disciplines to explore the topic of interest. Reports from basic to clinical and population research are suitable. Articles adopting a longitudinal approach or reporting data from life-long interventions/observations in the exploration of the theme will be given special consideration. Potential topics include, but are not limited to: • Description of patterns of dietary protein consumption across life • Influence of dietary protein intake on the functional status of older people • Preclinical and clinical studies describing the mechanisms through which protein intake modifies muscle mass and function • Protein/amino acid supplementation interventions against sarcopenia, cachexia, or disease conditions associated with muscle wasting in old age • Disease-specific alterations modifying the effects of dietary protein intake on skeletal muscles • Effects of the interactions of dietary protein intake and gut microbiota on skeletal muscles]